Memory awareness in patients with major depressive disorder - Mendes, Tiago (2021)
Subjective Memory Complaints (SMC) along with cognitive deficits are frequently observed in patients with Major Depressive Disorder (MDD). The relationship between SMC and objective memory performance in patients with MDD was evaluated, in comparison with patients with Mild Cognitive Impairment due to Alzheimer's Disease (MCI-AD) and healthy controls (HC).